2005
DOI: 10.1016/j.jcrs.2004.10.046
|View full text |Cite
|
Sign up to set email alerts
|

Causes of spherical aberration induced by laser refractive surgery

Abstract: This nontoric eye model, which separates the effects of differences in ablation efficiency and biological corneal surface change quantitatively, explains how spherical aberration is induced after myopic and hyperopic laser refractive surgery. With the corneal topographic data, this model can be incorporated into the ablation algorithm to decrease induced spherical aberrations, improving the outcomes of conventional and customized treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
93
1
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(100 citation statements)
references
References 20 publications
4
93
1
2
Order By: Relevance
“…After myopic procedures, induced spherical aberrations tend to be positive and correlated with the magnitude of intended correction. [5][6][7][8] The increase in spherical aberration influences the visual function of the patient, 4,9 as measured by contrast-sensitivity function (CSF) and low luminance visual acuity. Further, if significant spherical aberration is induced by refractive surgery, the correction of defocus could also be affected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After myopic procedures, induced spherical aberrations tend to be positive and correlated with the magnitude of intended correction. [5][6][7][8] The increase in spherical aberration influences the visual function of the patient, 4,9 as measured by contrast-sensitivity function (CSF) and low luminance visual acuity. Further, if significant spherical aberration is induced by refractive surgery, the correction of defocus could also be affected.…”
Section: Introductionmentioning
confidence: 99%
“…Jiménez et al 13 showed that pre-and postsurgery asphericity values scale with the cube of pre-to postcorneal radii. For an aspherical surface, spherical aberration is proportional to asphericity (Q ¼ pÀ1), 8 which accounts for the increase in spherical aberration. However, when the exact Munnerlyn formula is used, without ablation efficiency reduction, Gatinel et al 14 reported that the postsurgery corneal asphericity does not increase.…”
Section: Introductionmentioning
confidence: 99%
“…All ablations were non-wavefront-guided but were based on aspheric 25 aberration-neutral (Aberration-Free TM ) profiles (and not on the profiles proposed by Munnerlyn 26 ) to balance the induction of spherical aberration 27,28 (prolateness optimization 29,30 ). This approach included a multidynamic aspherical transition zone, aberration and focus shift compensation due to tissue removal, pseudo-matrix-based spot positioning, enhanced compensation for the loss of efficiency; 31 all based on theoretical equations validated with ablation models and clinical evaluations.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated that this causes the increase in spherical aberration after LASIK surgery. [25][26][27] . Our multizone analysis reveals that the actual increase in the Q values in the optical zone is even greater ͑about +1͒.…”
Section: One Examplementioning
confidence: 99%